Saving the Lives of Asphyxiated Newborns in Public Health Facilities: An Implementation Research - Shinde S; Tiruneh F; Abdissa D (Dove Medical Press, 2022)
Sanjay Shinde, Firew Tiruneh, Dinaol Abdissa Department of Midwifery, College of Health Sciences, Mizan-Tepi University, Mizan Teferi, EthiopiaCorrespondence: Sanjay Shinde, Department of Midwifery, College of health Sciences, Mizan Tepi university, Mizan Teferi, Ethiopia, Email mscshinde@gmail.comBack Ground: Globally, 2.6 million children died in their first month of life-approximately 7 000 newborn deaths per day-with approximately one million dying on the first day and nearly one million dying within the next six days. Perinatal asphyxia plays a significant role in this mortality. Even those who survive will suffer from mental retardation and other complications. One programme to save the lives of asphyxiated newborns is "Helping Baby Breathe." However, it has yet to be successful in Ethiopia.Objective: To assess the status of implementation of helping baby breath and to design alternative best way to improve the service, in public hospitals of Bench-Maji, Kaffa and Sheka zones.Methods: Concurrent triangulation was used in the design. We used a phenomenological and descriptive cross-sectional study design. The subjects of the study were key informants, postnatal mothers, and health care providers in the delivery ward. Atlas Ti and SPSS software were used to analyze qualitative and quantitative data, respectively.Results: We reported on the knowledge and skills of health care providers in neonatal resuscitation in this study. The findings revealed that participants with good knowledge and skill were 54% and 27%, respectively. A number of contextual factors that may be impeding neonatal resuscitation were also identified qualitatively.Conclusion: The majority of health care providers' skill and knowledge of neonatal resuscitation were far below the minimum expected competency.Keywords: saving the life, asphyxiated, newborn, public health facilities, implementation